'I only interpret the content and ask practical questions when necessary.' Interpreters' perceptions of their explicit coordination and personal pronoun choice in telephone interpreting. (4th July 2021) - Wang, Jihong
ABSTRACT: This questionnaire-based survey study explored 465 telephone interpreters' perceptions of their explicit coordination in interpreter-mediated telephone communication, their self-reported personal pronoun choice in telephone interpreting, their perceptions of clients' understanding of the interpreter's role, and their experience of clients' personal pronoun choice. The majority of telephone interpreters responded that they only explicitly coordinated the triadic communication as necessary. Moreover, most telephone interpreters reported that they often used the first person pronoun in telephone interpreting; however, some telephone interpreters responded that they switched to the third person pronoun occasionally to avoid confusion and meet clients' special needs. From telephone interpreters' perspective, not all users were familiar with the interpreter's role, thus highlighting the need for client training. Furthermore, most telephone interpreters indicated that often clients used a mixture of both the second person pronoun and the third person pronoun to address each other over the phone.